A tale of three cities: Aesthetico-cultural cosmopolitanism as a new capital among youth in Paris, São Paulo, and Seoul. (August 2021) - Cicchelli, Vincenzo; Octobre, Sylvie; Riegel, Viviane; Katz-Gerro, Tally; Handy, Femida
This article adds to the literature on the consequences of cultural capital at the age of cultural globalization by analyzing the ways youth engage in globalized cultural consumption in three cities – Paris, São Paulo, and Seoul. Drawing on cosmopolitanism as an aesthetic and cultural stance of openness and on global cultural consumption as providing youth with cosmopolitan skills, we compare the uses of aesthetico-cultural cosmopolitanism in three contexts. We offer an original account of different uses of cosmopolitan cultural skills, which, to varying degrees in the three contexts, signal generational belonging, social distinction, educational and professional success, and personal eruditeness and fulfillment. Analysis of recent interviews with 80 youth in each city reveals distinct uses of aesthetico-cultural cosmopolitanism: as a vehicle for self-development (either empowerment or Bildung ) in Paris, as a means for the cultivation of social capital for personal status in São Paulo, and as human capital serving for labor market entry and attainment in Seoul. Our findings accentuate that even with the prevalence of cultural globalization in global cities, the functions of cosmopolitan skills remain highly dependent on educational, institutional, cultural, and political contexts at the national level, which create different incentives and opportunities or barriers to experiencing otherness and developing new types of cultural capital.